Implementation of Good Corporate Governance (GCG) in the Field of Securing Plantation Assets - Junaedi Junaedi (Journal La Sociale, 2020)
This article discusses the implementation of Good Corporate Governance (GCG) in the Field of Securing Plantation Assets, especially at PT Perkebunan Nusantara (PTPN) IV. Good Corporate Governance (GCG) in the area of ​​securing assets in PTPN IV can be measured by the three elements of the legal system, namely: the legal substance (the Forestry Law); its legal structure (Law Enforcement Officials: Forestry and Police PPNS); corporate legal culture. The three systems are interrelated with one another. Systemic law enforcement efforts must pay attention to the elements of the legal system because it is the essence of law enforcement. the findings in the field of plantation crime mode are massive and organized. With regard to theft of oil palm, many people believe that it is often carried out by oil palm ninja (simple crime), but in reality theft by "oil palm ninja" is about 10% to 15% only. In reality, there is an oil palm mafia operating in PTPN IV's estates which holds 85% of these oil thieves. 90% organized / serious crime. The criminal act of theft and embezzlement of oil palm FFB (Fresh fruit bunches) in the PTPN IV area is massive and can be categorized as very critical.